Concept and Implementation of Online Game-Based Learning Approach in Distance Learning - Esti Jayanti (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
Education is an endeless learning process either formally or nonformally. To achieve student’s goal, they must develop their potential. This potential can be achieve through learning that is education. In this pandemic situation, student’s doing online learning. But students don’t have any meaningfull learning in this activities. Students have been enamored in online games. The purpose of this study is to describe 1. Online game-based learning approach, 2. Implementation of a online game-based learning in distance learning. The result of this study are: (1) Online game-based learning is a learning approach based on software.; (2) the implementation of the online game-based learning approach in distance learning is combining data collection, system analysis, coding, implementation, and maintenance. The conclusion of this study are online game-based learning is an educational system where teacher can apply an online game for cognitive interest and learning motivation that students need.